9th annual Calgary Graphics. - Graphics Exhibition Calgary (Calgary. : Calgary Graphics)
Caiserman-Roth, Ghitta ; Foster, Velma ; Weldon, Phyllis ; Wright, Don ; Blackwood, David ; Bell, Alistair ; Grey, Jerry ; Ellemers ; Kristmanson, Lawrence ; Kipling, Ann ; Harris, Joyce ; Haeseker, Sandy ; Taïra ; Bobak, Bruno ; Weinstein, Alan ; Coburn-Donnelly, K. ; Mabie, Don ; compernol, Lucien ; Lacroix, Richard
9th annual Calgary Graphics, February 5-20
boek